(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the importance of heavy metals in meadow-oasis soils and the plant Indigofera tinctoria, belonging to the family of legumes (Febaceae), the history of research, and the permissible regulatory concentrations are discussed. In particular, soil and plant samples were irradiated with a neutron flux of 5 • 1013 neutrons/cm2 seconds in an atomic reactor, and the amounts of elements were determined based on the half-life periods of chemical elements. The concentration of heavy metals cobalt (Co), nickel (Ni), zinc (Zn), molybdenum (Mo) in soil and indigofera tinctoria were determined and compared. was studied.